PARENTAL SUPPORT AND CAREER ORIENTATION AS DETERMINANTS OF STUDENTS’ FURTHER EDUCATION DECISIONS AT SMK NEGERI 1 TAMBUSAI - Ansori B; Agus Basuki (Journal of Education and Teaching Learning, 2026)
This study aims to determine the influence of parental support and career orientation on the decision-making process regarding further education among students at SMK Negeri 1 Tambusai. This is an associative quantitative study. The study population consists of all 308 twelfth-grade students at SMK Negeri 1 Tambusai. The sampling technique used was random sampling, meaning the entire population was included in the study sample. Questionnaires were used as instruments to measure parental support, career orientation, and decisions regarding further education. Data analysis employed multiple linear regression. The results indicate a significant influence of parental support and career orientation on the decisions regarding further education among students at SMK Negeri 1 Tambusai, with a linearity test significance value (sig) of 0.000 (< 0.05). The calculated F-value of 19,531.925 indicates that both independent variables simultaneously influence the dependent variable, and the significance level (sig) of 0.000 is less than 0.05; thus, the hypothesis stating the existence of a simultaneous influence between the variables is supported. This means that the higher the level of parental support and the better the students’ career orientation, the more mature and appropriate their decisions regarding further education will be.